Changes in sleep predict changes in depressive symptoms in depressed subjects receiving vortioxetine: An open-label clinical trial. (November 2019) - Cao, Bing; Park, Caroline; Rosenblat, Joshua D; Chen, Yan; Iacobucci, Michelle; Subramaniapillai, Mehala; Mansur, Rodrigo B; Zuckerman, Hannah; Lee, Yena; McIntyre, Roger S
Background: Sleep disturbances are frequently reported in patients with major depressive disorder. We aimed to investigate the effects of vortioxetine on sleep quality and association between changes in sleep and treatment response. Methods: This study is a post-hoc analysis of a clinical trial that sought to evaluate the sensitivity to cognitive change of THINC-integrated tool in patients with major depressive disorder. In total, 92 patients (aged 18 to 65) meeting Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition criteria for moderate or severe major depressive disorder and 54 healthy controls were included. All patients received open-label vortioxetine (10–20 mg/day, flexibly dosed) for 8 weeks. Herein, the primary outcomes of interest were changes in sleep, as measured by the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Insomnia Severity Index, between weeks 0, 2, and 8. The association between changes in sleep and depressive symptom severity was secondarily assessed. Results: We observed that sleep, as indicated by scores of Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Insomnia Severity Index, was significantly poorer in patients with major depressive disorder compared to healthy controls at weeks 0, 2, and 8 ( p < 0.05). Among patients with major depressive disorder, we observed significant improvements on the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Insomnia Severity Index between weeks 0 and 8 ( p < 0.05). We observed a significant association between improvements on the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, and Insomnia Severity Index and improvement of depressive symptoms. Conclusion: Improvement of depressive symptoms in major depressive disorder patients treated with vortioxetine was associated with significant improvements in sleep. Furthermore, improvements in sleep were predictive of antidepressant response and were linearly correlated with improvement in overall depressive symptom severity.